Syringocystadenoma papilliferum (deep seated horiostomatous): a case report - Paudel, D; Midha, A; Samdurkar, A; Kumar, A (Journal of Universal College of Medical Sciences, 2014)
Syringocystadenoma papilliferum (SCAP) is a rare benign adenexal tumor that frequently shows apocrine differentiation. SCAP usually occurs in the head and neck region in the children. Here in we report a case of 22 years female with SCAP occurring in deeper portion of the neck. The clinical, histopathological features and differential diagnosis of SCAP are also described. DOI: http://dx.doi.org/10.3126/jucms.v2i1.10491 Journal of Universal College of Medical Sciences (2014) Vol.2(1): 38-40